Product innovation and optimization of the role of HR on the Snackqu Business Unit in Indonesia - Mauleka, Muhammad Iqbal; Rahman, Moh. Abd. (Technium Social Sciences Journal, 2021)
Snack Qu (SQ) is a business unit that is engaged in the light food business or what is often referred to as snacks with the concept of serving Indonesian flavors, among which the products are Cacang (bottled nuts with various Indonesian flavors). The Snack Qu business unit must develop a sales strategy that is in accordance with the development of industry 4.0, for this reason what is used in this business concept is direct and online marketing. Direct marketing is also carried out through SnackQu partner shops, which are located in the Sleman area. For the human resources of the snackqu business unit in the early days of its establishment, Snackqu only consisted of three members, namely the owner who was also an operation and two staff who were engaged in production and marketing. In the development in the field, the Snack business unit turns out to have several realities that are not in accordance with what was planned. Like the first product that was not in demand in the market, it required Snackqu to stop production and make other product innovations. The role of human resources, which is limited in number with an erratic workload, is also an obstacle so that it is necessary to optimize the role of the company structure. With this gap, the best solution is sought to develop a future Snackqu business unit for the HR sector by utilizing beer theory about role clarity theory and structural theory. The solutions taken were in the form of developing clear SOPs between staff and leaders, transferring marketing staff to operational staff, and building partnerships with best friend SQ (resellers). For the marketing field, Snack Qu presents several solutions. Keywords: Role Optimization, Product Innovation, Snackq